2015
DOI: 10.1111/adb.12301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated social defeat on adolescent mice on cocaine‐induced CPP and self‐administration in adulthood: integrity of the blood–brain barrier

Abstract: Social stress in adulthood enhances cocaine self-administration, an effect that has been related with an increase in extracellular signal-regulated kinase and p38α mitogen-activated protein kinase phosphorylation. A detrimental effect of cocaine on blood-brain barrier (BBB) integrity has also been reported. This study evaluates the effects of repeated social defeat (RSD) during adolescence on the reinforcing and motivational effects of cocaine in adult mice and the changes induced by RSD on BBB permeability. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 62 publications
4
49
1
Order By: Relevance
“…Therefore, a decrease in amphetamine or morphine rewarding effects was reported in rodents exposed to chronic mild stress [31,32], and a neonatal model of stress produced a decrease in the rewarding effects of cocaine evaluated in the CPP [33]. However, enhanced rewarding effects of cocaine were also found in adolescent mice exposed to stress by social defeat [19]. The discrepancy in these previous results may be due to the characteristics of stressful situations in terms of the frequency and duration of stress as well as the age at which the stress situation took place.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, a decrease in amphetamine or morphine rewarding effects was reported in rodents exposed to chronic mild stress [31,32], and a neonatal model of stress produced a decrease in the rewarding effects of cocaine evaluated in the CPP [33]. However, enhanced rewarding effects of cocaine were also found in adolescent mice exposed to stress by social defeat [19]. The discrepancy in these previous results may be due to the characteristics of stressful situations in terms of the frequency and duration of stress as well as the age at which the stress situation took place.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some behavioural studies have suggested that adolescents are hyposensitivity to psychostimulants effects relative to adult rats [34,35]. Accordingly, in a recent study evaluating the rewarding effects of cocaine in the conditioned place preference, an effective dose of 25 mg/kg of cocaine revealed a significant effect in adolescent OF1 mice [19]. Conversely, the higher dose used in the present study was 15 mg/kg and only a marginally effect was observed in the CPP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, insufficient mPFC dopamine activity during reward processing is associated with both increased impulsive choice (Yates et al, 2014) and perseveration in conditioned response despite changes in reward contingency (Floresco, 2013). In accordance with this, rats defeated in adolescence show enhanced preference for psychostimulantassociated cues even when the drug is no longer available (Burke et al, 2011;Rodriguez-Arias et al, 2017), along with greater alcohol and cocaine self-administration (Burke & Miczek, 2015;Rodriguez-Arias et al, 2017;Rodríguez-Arias et al, 2017). Findings from the current and previous studies suggest that targeting D2 autoreceptors along with DAT to restore dopamine availability in the mPFC could lead to more efficacious treatment of the cognitive deficits seen in adult neuropsychiatric disorders promoted by periadolescent stress (Watt et al, 2017).…”
Section: Discussionmentioning
confidence: 81%